2018
DOI: 10.1111/1742-6723.12921
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Best practice management of common shoulder injuries and conditions in the emergency department (part 4 of the musculoskeletal injuries rapid review series)

Abstract: Shoulder injuries are a commonly presenting complaint to the ED. In the absence of an obvious deformity, they can be difficult to assess and definitively diagnose because of the multiple structures that cause shoulder pain, the acuity and severity of pain and the lack of range of motion in the ED setting. The quality of ED care provided to patients with musculoskeletal shoulder pain is crucial to ensure the best possible outcomes for the patient. This rapid review investigated best practice for the assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 78 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…This replicates the findings of Hsiang et al [6] As triage has been found to increase ED referral likelihood, a short set of triage questions should be implemented by MUCCs to ensure that patients seek care at the appropriate care setting. Strudwick et al [13][14][15][16][17][18] published a series of papers recommending history questions and red flags for a variety of orthopedic conditions, however no simple set of triage questions has been recommended for use in the MUCC setting. While we do not expect a receptionist to perform a detailed history over the phone, we recommend that a short set of triage questions be utilized to prevent delays in care caused by directing patients to a MUCC instead of the ED.…”
Section: Discussionmentioning
confidence: 99%
“…This replicates the findings of Hsiang et al [6] As triage has been found to increase ED referral likelihood, a short set of triage questions should be implemented by MUCCs to ensure that patients seek care at the appropriate care setting. Strudwick et al [13][14][15][16][17][18] published a series of papers recommending history questions and red flags for a variety of orthopedic conditions, however no simple set of triage questions has been recommended for use in the MUCC setting. While we do not expect a receptionist to perform a detailed history over the phone, we recommend that a short set of triage questions be utilized to prevent delays in care caused by directing patients to a MUCC instead of the ED.…”
Section: Discussionmentioning
confidence: 99%
“…One group from Australia provided recommendations for assessment, imaging, treatment, referrals, and followup for common orthopaedic conditions by assembling guidelines from systematic reviews. However, these reviews were not performed in urgent care or emergency settings [26][27][28][29][30][31]. These reviews covered foot and ankle injuries, low back pain, hand and wrist injuries, knee injuries, neck injuries, and shoulder injuries.…”
Section: What We (Think) We Knowmentioning
confidence: 99%